The impact of nutritional status and maternal behavior on infant growth - Erry Yudhya Mulyani; Idrus Jus'at; Anindya Billa Mustika (Alma Ata University Press, 2022)
Background: Maternal behaviour during pregnancy is closely related to the condition of the fetus. Malnutrition in pregnant women can cause Low Birth Weight Babies (LBW) and also a decrease in the level of intelligence. The prevalence of stunting in 2021 decreased by 1.6 from 2019, that shows from 27.7% to 24.4%.Objectives: This study aims to determine the impact of nutritional status and maternal behaviour on infant growth in West Jakarta.Methods: This study was a cross-sectional, starting on July 2017 until January 2018. A total of 66 subjects of pregnant women aged 18-35 years chosen to take part in the study from their 37th weeks of pregnancy to delivery. Drinking alcohol, traditional herbs, medicines, and smoking are indicators of maternal behaviour. Maternal IGF-1 concentrations, body weight, body length, and infant heart rate were indicators of infant growth. Chi-Square test and Independent T-Test were used for the statistical analysis.Results: The subjects showed a mean of 26.0±4.8 years old, body height of 154.0±4.9 cm, body weight in third pregnancy of 66.4±11.3 kg, BMI of 22.6±3.7 kg/m2, MUAC of 27.2±3.3 cm, and body temperature of 36.2±1.3°C. Maternal behaviour and nutrional status did not significantly affect infant growth (p≥0.05). However, MUAC was a factor that affected to heart rate in infants (p<0.05).Conclusions: Nutritional status is one of indicator that affects to infant growth; therefore, pregnant women need to more attention to keep their nutritional status, nutritional intake and healthy living behaviour during pregnancy.